Anxiety/Uncertainty Management and Communication Accommodation in Women's Brief Dyadic Conversations With a Stranger: An Idiodynamic Approach. (July 2019) - MacIntyre, Peter D.
This study uses a combination of anxiety/uncertainty management theory and communication accommodation theory perspective to examine differences in the ways women converse with men or with other women. The study uses an innovative approach, the idiodynamic method, to gather detailed data on a per-second timescale. Participants ( n = 24) were randomly assigned to one of the two types of dyads: female–female or male–female. They then engaged in a videotaped conversation lasting approximately 2 to 5 min. Immediately afterward, participants watched the video of their conversation in separate rooms, during which each provided continuous, dynamic ratings of their anxiety level, and that of their partner, throughout the conversation. Participants were interviewed about the reasons for changes in their ratings of both themselves and their conversational partner. Following a grounded theory approach to analysis, six themes emerged from the interviews: awareness of the camera and researchers, comparison of self and partners, self-judgment, worry about other's judgment, disinterest, and reaction to miscommunication. The data show that communication accommodation was done differently in the female-only versus female–male pairs, which might reflect processes involving uncertainty, group identification, and continuously negotiated meaning. There is value in using methods that investigate communication processes in real time because doing so allows instances of proposed theoretical differences between genders to emerge in actual conversation between persons.